2019
DOI: 10.1111/his.13839
|View full text |Cite
|
Sign up to set email alerts
|

Gene fusion involving the insulin‐like growth factor 1 receptor in an ALK‐negative inflammatory myofibroblastic tumour

Abstract: Aims Inflammatory myofibroblastic tumour (IMT) is a soft tissue tumour primarily affecting children and young adults. Approximately 50% of IMTs have gene fusions involving the receptor tyrosine kinase (RTK)‐encoding ALK gene, providing a molecular rationale for treating IMT patients with unresectable tumours with tyrosine kinase inhibitors (TKI). However, a subset of IMT instead displays fusions affecting other RTKencoding genes, so far including NTRK3, PDGFRB and ROS1. Also, IMTs with variant RTK fusions may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Kekeeva et al discovered a fusion transcript of IGF1R‐TTC23 in bladder cancer that encodes the amino‐terminal extracellular region of IGF1R fused to TTC23 whose function is yet unknown. Piarulli et al reported on a patient with an ALK‐negative inflammatory myofibroblastic tumor carrying FN1‐IGF1R fusion transcript. Both groups identified IGF1R fusion candidates from RNA‐seq data but did not confirm the corresponding genomic rearrangements nor examine the transforming ability of the protein products.…”
Section: Discussionmentioning
confidence: 99%
“…Kekeeva et al discovered a fusion transcript of IGF1R‐TTC23 in bladder cancer that encodes the amino‐terminal extracellular region of IGF1R fused to TTC23 whose function is yet unknown. Piarulli et al reported on a patient with an ALK‐negative inflammatory myofibroblastic tumor carrying FN1‐IGF1R fusion transcript. Both groups identified IGF1R fusion candidates from RNA‐seq data but did not confirm the corresponding genomic rearrangements nor examine the transforming ability of the protein products.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of IMTs carry translocations in a closely related gene, ROS1 3 . In addition, some IMTs harbor fusions involving other tyrosine kinase encoding genes, e.g., NTRK3, RET, PDGFRb , and IGF1R 2,4‐6 . The detection of these rearrangements is of high clinical value, as it ensures the reliability of morphological IMT diagnosis and provides grounds for therapeutic interventions 7‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, some IMTs harbor fusions involving other tyrosine kinase encoding genes, e.g., NTRK3, RET, PDGFRb, and IGF1R. 2,[4][5][6] The detection of these rearrangements is of high clinical value, as it ensures the reliability of morphological IMT diagnosis and provides grounds for therapeutic interventions. [7][8][9] Current diagnostic approaches are based on immunohistochemical (IHC) detection of activated kinases, FISH-based analysis of gene rearrangements, and identification of translocations by the next-generation sequencing (NGS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Genetically, IMT is a heterogeneous disease driven by fusions that affect the receptor tyrosine kinase genes, including ALK, ROS1, NTRK3, RET, 8 PDGFRβ and IGF1R. 12 Among them, ALK gene rearrangements were majorly encountered in 50-60% of IMT cases, and predominately occur in children and young adults. Moreover, the ALK gene also has the largest number of fusion partners.…”
Section: Discussionmentioning
confidence: 99%